FRI0185 Tofacitinib versus biologic treatments with and without methotrexate in patients with active rheumatoid arthritis who have had an inadequate response to traditional disease modifying anti-rheumatic drugs - a network meta-analysis. (23rd January 2014) - Vieira, M.C.; Wallenstein, G.V.; Bradley, J.D.; Gruben, D.; Koncz, T.; Zwillich, S.H.; Jansen, J.P.
Abstract : Background: Tofacitinib (CP-690, 550) is a novel, oral Janus kinase inhibitor that is being investigated as a targeted immunomodulator and disease-modifying therapy in rheumatoid arthritis (RA). Objectives: A network meta-analysis to evaluate the efficacy and safety of tofacitinib 5 and 10 mg BID relative to biologic disease-modifying anti-rheumatic drugs (DMARDs) in the treatment of RA patients who have shown an inadequate response to DMARDs (DMARD-IR), based on available randomised controlled trials (RCTs). Methods: Thirty-three RCTs evaluating tofacitinib and various biologic DMARDs, dosed as monotherapy or in combination with methotrexate (MTX) or another DMARD, were identified through a systematic literature search. Individual study efficacy data, based on American College of Rheumatology (ACR) responses at Mo 3 and 6, were combined with network meta-analyses. Comparisons of safety were based on rates of treatment withdrawal due to adverse events (AEs). Results: Both as monotherapy and in combination with MTX, tofacitinib 5 and 10 mg BID showed ACR responses comparable to currently available tumour necrosis factor inhibitors and tocilizumab at Mo 3 (see Table) and 6. Furthermore, in this analysis tofacitinib is at least as efficacious as abatacept, anakinra, and rituximab. Withdrawal rates from trials due to AEs were comparable. Conclusions: Based on analyses of available RCTs, tofacitinib has similar efficacy in improving signs and symptoms as biologic DMARDs for DMARD-IR patients. Further analyses are needed to explore the impact of factors that may impact the magnitude of the placebo response and confound comparative treatment effects in treatment of RA. Impact of factors that confound comparative treatment effects in treatment of RA needs to be explored (e.g. starting MTX dose, duration and number of prior DMARDs). Disclosure of Interest: M. Vieira Consultant for: Pfizer Inc, G. Wallenstein Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Bradley Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Gruben Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Koncz Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Zwillich Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Jansen Consultant for: Pfizer Inc